2015
DOI: 10.1007/s40011-015-0605-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Assessment of Hemato-Biochemistry, Oxidant/Antioxidant Status in Natural Canine Monocytic Ehrlichiosis Cases from Northern India

Abstract: The present study was aimed at detecting natural cases of canine monocytic ehrlichiosis (CME) by molecular and cytological methods and assessment of clinico-patho-biochemical parameters among the affected population. Nested polymerase chain reaction was found to be highly sensitive (47.7 %) in detecting the acute cases, followed by buffy coat (29.5 %) and blood smear examination (22.7 %). CME incidence rate was found to be 8.4 %. Hemogram revealed significant (P \ 0.01) depletion in the levels of hemoglobin, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…This fluctuation in the prevalence rate of E. canis across different agroecological zones of the country may be linked to the differences in sample size, diversity of infesting ticks and availability of competent tick vectors and host population that influence pathogen survival and in turn its prevalence rate. However, our findings are generally consistent with published literature that confirmed the presence of E. canis in the ixodid tick species and dog hosts from China, India, Korea, Philippines, Russia, Thailand, Portugal and Southeast Asia [ 3 , 54 60 ]. The 16S rRNA consensus sequences of E. canis shared homology and evolutionary history with identical isolates from Asia, Europe, North America and South America, suggesting that E. canis ' identical genotype is circulating in different tick species globally without geographic restrictions [ 60 64 ].…”
Section: Discussionsupporting
confidence: 92%
“…This fluctuation in the prevalence rate of E. canis across different agroecological zones of the country may be linked to the differences in sample size, diversity of infesting ticks and availability of competent tick vectors and host population that influence pathogen survival and in turn its prevalence rate. However, our findings are generally consistent with published literature that confirmed the presence of E. canis in the ixodid tick species and dog hosts from China, India, Korea, Philippines, Russia, Thailand, Portugal and Southeast Asia [ 3 , 54 60 ]. The 16S rRNA consensus sequences of E. canis shared homology and evolutionary history with identical isolates from Asia, Europe, North America and South America, suggesting that E. canis ' identical genotype is circulating in different tick species globally without geographic restrictions [ 60 64 ].…”
Section: Discussionsupporting
confidence: 92%
“…Kumar et al [15] reported 3.55 % prevalence of E. Canis in and around Meerut region of Uttar Pradesh. Behera et al [16] revealed that the nested polymerase chain reaction proved to be highly sensitive in detecting acute cases, followed by the buffy coat and blood smear examination. Singla et al [17] found that E. canis is second most tick born pathogen affecting dog following B. gibsoni in a Punjab state of India.…”
Section: Resultsmentioning
confidence: 99%